ROLE PUBLIC RELATIONS IN MARKETING YAMAHA MOTORCYCLE PRODUCTS TO THE PUBLIC - Anwar Sadat (SEAN Institute, 2020)
Humans are social creatures who live and must always socialize with other humans around them. Therefore, humans must have the courage to speak or what is commonly called public speaking. If humans have the courage to speak up, then humans can run public relations in a company. In this scientific paper of our group, we use descriptive quantitative research methods. Descriptive quantitative is a method in researching the status of human groups, an object, a condition, a system of thought or a class of events in the present mass, the aim is to make a descriptive, picture or painting about public relations in marketing products to the public. In the research that we did by collecting interview data, we found out how the strategies were created by several public relations actors. On average, these actors use online marketing strategies and also some do marketing by including brochures about products that are marketed to the company or the nearest office by providing discounts or attractive prices